Studies in law, politics, and society. Vol. 57 - Sarat, Austin (Emerald, 2012)
This volume of Studies in Law, Politics, and Society contains an international and interdisciplinary array of legal scholarship. Presenting diverse theoretical perspectives and methodological approaches, this work illuminates the laws response to its social context as well as the way law shapes that context. It shows how legal scholars contribute to public debate about contemporary issues as well as how they articulate the nature of rights and the limits of law.
Keywords: Law -- General.; Law -- Indigenous Peoples.; Law & society.; Legal system: general.; Sociological jurisprudence.; Political sociology.; elektronické knihy; electronic books